FAKTOR-FAKTOR YANG MEMPENGARUHI KONSUMSI SAYURAN RUMAH TANGGA PADA KAWASAN RUMAH PANGAN LESTARI DI PROVINSI JAWA TIMUR DAN SUMATERA SELATAN - Vyta W Hanifah; T Marsetyowati; A. Ulpah Ulpah , (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2014)
Factors Affecting Household’s Vegetables Consumption in the Area of Sustainable Food Reserved Garden (SFRG) Program in East Java and South Sumatera Provinces. Backyard has a potential to feed the family as vegetables cropland or fruit crops. Sustainable Food Reserved Garden Program (SFRG) was designed to increase the potential of backyard to provide sustainable cheap food. This study aimed to analyze the factors affecting household’s vegetables consumption in the area of SFRG program. The research was conducted in South Sumatra and East Java province in 2012, involving 60 respondents who have implemented the program in 2011 and 2012. Respondents were divided into three strata according yard size, which are stratum 1 (narrow), stratum 2 (medium) and stratum 3 (extensive). Data was collected through interviews using a structured questionnaire and focus group discussions with managers of the program. Afterwards, the data were analyzed descriptively and also by regression test to determine the factors affecting vegetable’s consumption in household level. The result showed that the variations of plants types tend to be uniform among the three strata such as pepper, eggplant and cabbage. In terms of the arrangement, narrow stratum was dominated by “vertikultur”, medium stratum by polybag and extensive stratum by seedbeds. SFRG program have contributed to household food expenditure between 2.5 to 8.8%. Multiple regression analysis showed that vegetables consumption has positively associated and significantly with vegetable production and monthly food expenditure. SFRG program is able to save household food expenses, especially for purchasing vegetables. Key words: Backyard, vegetables consumption, vegetables production, SFRG ABSTRAK Optimalisasi pemanfaatan lahan pekarangan penting untuk memenuhi kebutuhan pangan dan sayuran bagi keluarga. Melalui program Kawasan Rumah Pangan Lestari (KRPL) diharapkan dapat menyediakan pangan murah yang berkelanjutan. Penelitian bertujuan menganalisis faktor-faktor yang mempengaruhi konsumsi sayuran rumah tangga di Kawasan Rumah Pangan Lestari. Penelitian dilaksanakan di Provinsi Sumatera Selatan dan Jawa Timur tahun 2012 melibatkan 60 responden pelaksana program KRPL tahun 2011 dan 2012. Responden dibedakan ke dalam tiga strata berdasarkan luas pekarangan, yaitu strata 1 (sempit), strata 2 (sedang) dan strata 3 (luas). Pengumpulan data dilakukan dengan wawancara menggunakan kuesioner terstruktur dan Focus Group Discussion melibatkan pengelola program KRPL. Data dianalisis secara deskriptif dan kuantitatif. Uji regresi linier berganda digunakan untuk mengetahui faktor-faktor yang berpengaruh terhadap konsumsi sayuran pada keluarga. Hasil penelitian menunjukkan bahwa variasi jenis tanaman cenderung seragam antar strata, dengan tanaman dominan cabe, terong dan sawi. Penataan tanaman pada strata satu dominan vertikultur, strata dua menggunakan polibag dan strata tiga dengan bedengan. Kontribusi program KRPL terhadap pengeluaran pangan rumah tangga antara 2,5 - 8,8%. Hasil analisis uji regresi berganda menunjukkan konsumsi sayuran dipengaruhi secara nyata oleh produksi dan pengeluaran pangannya. Program KRPL mampu menghemat pengeluaran pangan rumah tangga terutama untuk pembelian sayuran. Kata kunci: Pekarangan, produksi sayuran, konsumsi sayuran, KRPL